Diseño de una estrategia de posicionamiento del Pájaro Azúl como marca país mediante la Asociación de Pequeños Productores del Cantón Echeandía - Almeida García, Cintya Alicia (2015)
This work qualification is aimed at small artisanal producers liquor Blue Bird holding its preparation in Echeandía Canton, located in the province of Bolivar, and have made this their main economic activity, keeping this tradition for over forty years. With the proposed development of a positioning strategy for this liquor, which is to be achieved is that the product is recognized in the national market as "country brand", highlighting its distinguishing features and, above all, that is a product that is made only in Ecuador, with raw material and labor Ecuadorian work. To do this, a business model that serves as a base so that it can improve production, marketing and distribution of Bluebird is presented.